Perlindungan Hukum Terhadap Konsumen Terkait Label Berbahasa Asing Dalam Suatu Produk Kosmetik - Made Isma Amanda Swadesi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2021)
As stipulated in the Consumer Protection Act no. 8 of 1999, many imported cosmetic products marketed in Indonesia are detrimental to consumers. The problems raised in this study are how the legal protection for consumers who are harmed due to the use of cosmetics labeled as foreign languages ​​and how is the legal responsibility of entrepreneurs to consumers who are harmed. The method used is a normative method or literature study using a legal approach and a conceptual approach. This research concludes that consumer legal protection can be implemented preventively and repressively. In addition to legal responsibility, business actors are also responsible for their actions and receive sanctions if their actions violate the law. Entrepreneurs who commit fraudulent actions are subject to sanctions or must carry out their civil, administrative and criminal responsibilities. These consumer disputes can be resolved out of court through conciliation, mediation and arbitration, and in courts and groups of victims can file a lawsuit class action.